Analisis Yuridis Perlindungan Hukum Terhadap Jual Belionline di Indonesia dan Malaysia - Lu Sudirman; Lily Haryati (Fakultas Hukum, Universitas Internasional Batam, 2017)
The development of the Internet led to the formation of the market buying and selling. The practice of buying and selling online is known as e-commerce. E- commerce (electronic commerce), a separate business mechanism that he was still whole corn. And the location of its merits is for the first time all people on earth have the same chance and opportunity to be able to do business with people all over the world. Methodology used in this research is the normative legal research -based comparative law. The data used in this study is a secondary data obtained from literature (library research). Once all the data is collected, then processed and analyzed to find the legal issues that are the object of study and conclude , then described descriptively. The results showed that Indonesia and Malaysia have had legislation setting a good enough in regulating the buying and selling online. Indonesia and Malaysia have similarities and differences within its authority, namely the recognition of online transactions, electronic signatures, the area prevailing law, the legitimate requirements of online transactions, consumer rights, and protection of personal data and privacy.